Factors Affecting Farmers’ Access to Agricultural Subsidy in Makwanpur and Dhading Districts of Nepal - Thapa, Sulochana; Panta, Hari Krishna; Poudel, Srijana; GC, Arun; Regmi, Kamal; Basnet, Manoj (SAARC Journal of Agriculture, 2023)
The government of Nepal has been providing high priority to subsidy programs to support farmers and boost the national economy. Increasing access to and effectiveness of the subsidy program is important to enhance growth of agricultural sector. However, there has always been a concern about access to and effectiveness of the subsidy programs to address the problem of farmers in Nepal. This study was carried out to determine the factors affecting farmers' access to the agricultural subsidy. For this, a multi-stage sampling method was employed, and altogether 120 commercial vegetable growers from Dhading and Makwanpur districts of Nepal were selected using simple random technique. Descriptive statistical tools and binary logistic regression were used to analyze the data. Out of the total sampled households, 55.83% had accessed at least one agricultural subsidy program, and the highest number of sampled households (39.17%) received the subsidy for agricultural tools. The result of binary logistic regression revealed that factors like ethnicity, membership in agricultural groups or co-operatives, farm visit by extension agents, and participation in agricultural training were significantly (p<0.01) influencing farmers' access to agricultural subsidy. Hence, the farmers are suggested to operate through agricultural groups or co-operatives, and the concerned authorities and policymakers should emphasize agricultural extension services and agricultural subsidy simultaneously for synergistic effects. SAARC J. Agric., 21(2): 263-276 (2023)